2023
DOI: 10.1038/s41467-023-39661-5
|View full text |Cite|
|
Sign up to set email alerts
|

Epidemiological drivers of transmissibility and severity of SARS-CoV-2 in England

Abstract: As the SARS-CoV-2 pandemic progressed, distinct variants emerged and dominated in England. These variants, Wildtype, Alpha, Delta, and Omicron were characterized by variations in transmissibility and severity. We used a robust mathematical model and Bayesian inference framework to analyse epidemiological surveillance data from England. We quantified the impact of non-pharmaceutical interventions (NPIs), therapeutics, and vaccination on virus transmission and severity. Each successive variant had a higher intri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Each new variant was associated with a sequential increase in the reproduction number, in alignment with similar studies into the transmission potential of each variant 10 .…”
Section: Resultsmentioning
confidence: 99%
“…Each new variant was associated with a sequential increase in the reproduction number, in alignment with similar studies into the transmission potential of each variant 10 .…”
Section: Resultsmentioning
confidence: 99%
“…During epidemics such as Ebola in West Africa, there was also evidence that transmission declined as populations can change their behaviour independently of top-down measures, in response to directly observed community infections and/or indirectly observed information [156] and similar changes in behaviour independent of interventions were observed for SARS-CoV-2 [157,54]. The extent to which behavioural feedback can influence the dynamics of a growing epidemic will depend on the relative timescale of epidemic growth versus delays from infection to outcome.…”
Section: Population-level Interventions 721 Prospective Analysis Of P...mentioning
confidence: 88%
“…As a result, they did not present the balance of risk integrating over the likely future of COVID-19 (i.e. eventual reopening with exit waves of infection [157]), and hence would have underestimated the benefits of vaccination. Subsequent work found that, given the severity of the Delta variant that caused waves in mid-2021, earlier vaccination with imperfect vaccine candidates (in this case because of reduced efficacy) was preferable in terms of hospitalisations and deaths averted to waiting months for other vaccine options [165].…”
Section: Case Study 18: Vaccine Benefits Vs Risk In a Dynamic Epidemicmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 5 6 7 8 Additionally, although omicron, the most recent variant, exhibits increased transmissibility than previous variants, it tends to result in milder disease severity. 9 10 Consequently, the mortality rates have significantly decreased recently. 3 …”
Section: Introductionmentioning
confidence: 99%